Split adhesion forming PIM complex hollow structure and preparation method thereof
Patent Information
- Application Number
- CN202611279579.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]为了解决现有PIM复杂中空件分体成形存在的防呆结构复杂、焊接/胶接密封性差、工序多、成本高的问题,本发明提供一种分体粘合成形PIM复杂中空结构件及其制备方法,可以在取消防呆结构的同时实现高强度、高密封性一体化成形
1、本发明的分体粘合成形PIM复杂中空结构件的方法,通过将复杂中空结构件拆分为多个分体坯体,再利用复配粘结剂降低表面张力、提升界面粘性,与粘接粉末复配形成粘接浆料涂覆于粘合面上,利用浆料粘力以及固液表面毛细力实现分体件物理结合,无需设计防呆结构,再经一体化脱脂、烧结直接成形为致密完整的复杂中空结构件。
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder injection molding technology, and in particular to a split-bonded PIM complex hollow structural component and its preparation method. Background Technology
[0002] Powder injection molding (PIM) is suitable for mass production of small, complex, and precision metal parts. For complex structural parts such as hollow, thin-walled, and irregularly shaped cavities, traditional processes often employ a process of separate injection molding, separate debinding, separate sintering, and then welding / adhesive assembly. However, this process has the following drawbacks: 1. A foolproof positioning structure needs to be designed, and the mold and forming process is difficult; 2. Welding is prone to poor sealing, corrosion, and deformation; it also results in low bonding strength and poor temperature resistance. 3. Numerous processes, high costs, and low yield; 4. It is difficult to meet the requirements of harsh working conditions such as immersion, high pressure, and high salt spray.
[0003] Therefore, developing a simple, reliable, and foolproof method for forming split-bonded PIM hollow parts has significant engineering value. Summary of the Invention
[0004] To address the problems of complex error-proofing structures, poor welding / adhesive sealing, numerous processes, and high costs associated with the separate molding of complex hollow PIM components, this invention provides a separate adhesive molding method for complex hollow PIM components and its preparation. This method can achieve high-strength, high-sealing integrated molding while eliminating the need for error-proofing structures.
[0005] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for split-bonding molding of complex hollow PIM structural components, comprising the following steps: (1) Design the complex hollow structure as at least two separate injection molded parts, and prepare the separate blanks separately by powder injection molding process; (2) Prepare adhesive slurry, wherein the adhesive slurry includes adhesive powder and compound adhesive; (3) Apply the adhesive slurry evenly to the bonding surface of each separate blank, and combine the separate blanks into a whole blank; (4) Perform an integral degreasing treatment on the entire blank; (5) The degreased blank is sintered as a whole to form a complex hollow structure.
[0006] This invention involves splitting complex hollow structural parts that cannot be directly PIM molded into two separate injection molded parts, either top and bottom or left and right, each with its own mold (if perfectly symmetrical, one set of molds can be omitted). Two separate preforms are obtained through injection molding. Then, an adhesive slurry is formed by combining adhesive powder and a compound adhesive. The compound adhesive reduces the surface tension of the bonding surface and improves the wettability and interfacial adhesion of the slurry, while the adhesive powder forms a transitional liquid phase during sintering to enhance interfacial bonding. Next, the adhesive slurry is uniformly coated onto the bonding surface of the separate preforms, using surface capillary force to physically adsorb and bond the two separate injection molded parts, eliminating the need for a foolproof design. Finally, the bonded preforms undergo an integrated degreasing process and sintering. The integrated degreasing process removes all organic components from the preforms and slurry, and the sintering process forms a dense and complete complex hollow structural injection molded part.
[0007] Optionally, in step (2), the compound adhesive includes at least two of polyethylene glycol, polyvinyl alcohol, acrylic resin and defoamer.
[0008] Optionally, in step (2), the mass percentage of the adhesive powder in the adhesive slurry is 50% to 65%.
[0009] Optionally, the adhesive slurry is composed of the following raw materials in weight percentages: 43.9% acrylic resin, 0.5% defoamer, and 55.6% 17-4H stainless steel powder.
[0010] Optionally, the adhesive slurry is composed of the following raw materials in weight percentages: 32% acrylic resin, 10% polyethylene glycol, 3% defoamer, and 55% 304L stainless steel powder.
[0011] Optionally, the adhesive slurry is composed of the following raw materials in weight percentage: 38% colloidal acrylic resin, 4% silicone defoamer, 6% polyvinyl alcohol, and 52% aluminum nitride ceramic powder.
[0012] Optionally, in step (2), the bonding powder is the same as the matrix powder in the split blank.
[0013] Optionally, in step (2), the bonding powder is a differentiated melting point powder whose melting point is no more than 50°C higher than that of the matrix powder in the split blank.
[0014] Optionally, in step (5), the temperature of the integral sintering treatment is not higher than the melting point of the matrix powder in the split blank, and not lower than the melting point of the differentiated melting point powder.
[0015] Optionally, in step (5), the heat preservation time of the integral sintering treatment is 1 to 4 hours, and after sintering is completed, the furnace is slowly cooled to room temperature.
[0016] Optionally, in step (3), the coating thickness of the adhesive slurry is 0.02~1mm.
[0017] When coating, the appropriate coating machine can be selected according to the different materials of the product. A three-axis automatic dispensing machine or a doctor blade coating machine can be selected to perform the bonding operation of the solid-liquid interface. After the two hollow parts of the separately injected product are bonded together, they are tightly bonded under the action of gravity and capillary force on the solid-liquid surface. Then, integrated degreasing and sintering are performed. The post-processing is the same as the normal PIM molding process.
[0018] By controlling the coating thickness of the adhesive paste to 0.02~1mm, the bonding strength can be guaranteed without affecting dimensional accuracy.
[0019] Optionally, the method further includes a step of roughening the bonding surface of the split blank before step (3).
[0020] By grinding and roughening the bonding surface of the split blanks to ensure a certain roughness, and controlling the surface roughness to 1.0~1.9μm, the wetting and bonding effect of the adhesive slurry can be improved, so that the two split blanks can be better bonded and formed.
[0021] Optionally, the matrix powder in the split blank is MIM metal powder or ceramic powder.
[0022] Optionally, the MIM metal powder is 17-4PH stainless steel metal powder or 316L stainless steel metal powder.
[0023] Optionally, the ceramic powder includes zirconia ceramic powder or aluminum nitride ceramic powder.
[0024] Optionally, in step (4), the integrated degreasing process adopts a combined process of catalytic degreasing and thermal degreasing.
[0025] Optionally, the catalytic degreasing temperature is 120~160℃ and the degreasing time is 4~12h.
[0026] Optionally, the degreasing temperature of the hot degreasing is ≤650℃, and the heat preservation time of the hot degreasing is 1.5~2h.
[0027] Secondly, the present invention provides a complex hollow structural component, which is manufactured using the aforementioned method for split-bonding and forming PIM complex hollow structural components.
[0028] Optionally, the complex hollow structural component is a thin-walled or medium-thick-walled structural component, a spiral-patterned structural component, or an irregularly shaped closed cavity type PIM precision part.
[0029] The beneficial effects of this invention are as follows: 1. The method of split bonding molding of complex hollow PIM structural parts of the present invention involves splitting the complex hollow structural parts into multiple split blanks, then using a compound adhesive to reduce surface tension and increase interfacial adhesion, and compounding it with adhesive powder to form an adhesive slurry which is coated on the bonding surface. The physical bonding of the split parts is achieved by utilizing the adhesive force of the slurry and the capillary force of the solid-liquid surface. No foolproof structure design is required. After integrated degreasing and sintering, it is directly formed into a dense and complete complex hollow structural part.
[0030] 2. The present invention uses the same matrix powder as the powder blank or a powder with a different melting point in the adhesive slurry. During sintering, a transitional liquid phase can be formed on the bonding surface to achieve interfacial metallurgical bonding, which completely solves the problems of low bonding strength, poor welding sealing, and easy deformation and corrosion of traditional adhesives.
[0031] 3. The complex hollow structural components prepared by this invention form complete and continuous grains at the bonding interface, exhibiting excellent mechanical properties, corrosion resistance, and sealing performance at the bonding surface. They are suitable for use in harsh working conditions such as immersion, high pressure, and high salt spray, and have extremely strong versatility and practicality.
[0032] 4. The preparation process of the present invention has low cost, shortened steps, and improved yield, making it suitable for mass production and applicable to the production of complex hollow parts such as thin-walled / medium-thick-walled, spiral, and irregularly shaped cavities. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] For the terms defined below, unless a different definition is given elsewhere in the claims or this specification, these definitions shall apply. All numerical values, whether explicitly indicated or not, are defined herein as being modified by the term "about." The term "about" generally refers to a range of numerical values that a person skilled in the art would consider equivalent to the stated values to produce substantially the same properties, functions, results, etc. A range of numerical values indicated by a low value and a high value is defined as including all numerical values included within that range and all subranges included within that range.
[0035] Unless otherwise specified, the experimental methods used in the following examples and / or comparative examples are conventional methods; the materials and reagents used can be purchased commercially unless otherwise specified.
[0036] The mass percentages of each component mentioned in the embodiments and / or comparative examples of this invention refer not only to the mass ratio between the components, but also to the specific content of each component. Therefore, any scaling up or down of the content ratios between the components mentioned in the embodiments of this invention is within the scope disclosed in the specification of the embodiments of this invention. The mass units mentioned in the specification can be known mathematical mass units such as mg, g, and kg.
[0037] Example 1 Example 1 provides a method for split-bonding molding of complex hollow PIM structural parts, used to prepare irregularly shaped hollow thin-walled hydraulic valve structural parts, including the following steps: (1) Preparation of split blanks.
[0038] The target irregularly shaped hollow thin-walled hydraulic valve structural component was symmetrically disassembled into upper and lower split structures. 17-4PH stainless steel powder was used as the matrix material, combined with a standard PIM binder (polyoxymethylene + low-density polyethylene plastic matrix composite system). The injection molding raw materials included the following volume fractions: 62.0 vol% 17-4PH stainless steel powder + 30.0 vol% POM + 6.0 vol% LDPE + 1.2 vol% HDPE + 0.8 vol% EVA (ethylene-vinyl acetate copolymer). Two split preforms were injection molded separately using a metal powder injection molding process. The injection temperature was 190℃, the injection pressure was 120MPa, and the holding time was 5s, resulting in split preforms with acceptable dimensional accuracy and a smooth surface.
[0039] Subsequently, the bonding surfaces of the two separate blanks were finely polished using 800-grit metallographic sandpaper to control the surface roughness to 1.2~1.8μm.
[0040] (2) Prepare adhesive mortar.
[0041] The adhesive slurry uses 17-4PH stainless steel powder as the bonding powder (the same as the matrix powder in the split blank). The mass ratio of the adhesive slurry is: 43.9% acrylic resin, 0.5% polyether-based silicone-free defoamer, and 55.6% 17-4H stainless steel powder. All components are added to a vacuum mixer and stirred at room temperature for 30 minutes at a stirring speed of 85 r / min to prepare a uniform, agglomerated adhesive slurry.
[0042] (3) Adhesive assembly and forming.
[0043] Precision coating equipment is used to evenly coat the bonding surfaces of the two separate blanks, controlling the coating thickness to 0.1mm. After coating, the two separate blanks are quickly and precisely bonded together, relying on the capillary force of the slurry surface and the interfacial adhesion to automatically bond and position themselves. After standing at room temperature for 15 minutes, the separate blanks are initially physically fixed without any misalignment or displacement.
[0044] (4) Integrated degreasing treatment.
[0045] The assembled green body is subjected to a combined process of oxalic acid catalytic degreasing and thermal degreasing. First, catalytic degreasing is performed at a temperature of 150℃ for 8 hours. Then, thermal degreasing is performed by raising the temperature to 580℃ and holding it for 2 hours to completely remove the binder and organic components of the slurry in the green body and avoid oxidation and deformation of the green body.
[0046] (5) Integrated sintering treatment.
[0047] After degreasing, integral sintering is carried out at a temperature of 1270℃ for 2-3 hours. The furnace is then cooled to room temperature to obtain an integral, complete hollow structural component.
[0048] The finished product has a dimensional accuracy of ±0.05mm, a tensile strength of 920MPa at the mating surface, excellent sealing performance, no rust after more than 48 hours of salt spray testing, and a yield rate of 98%.
[0049] Example 2 Example 2 provides a method for split-bonding molding of complex hollow PIM structural components, used to prepare irregularly shaped hollow thick-walled automotive steering gear structural components, including the following steps: (1) Preparation of split blanks.
[0050] The target irregularly shaped, hollow, thick-walled automotive turnaround component was symmetrically divided into two separate structures, left and right. 316L stainless steel powder was used as the matrix material, combined with a standard PIM (polyoxymethylene + low-density polyethylene) binder. The injection molding compound consisted of the following volume fractions: 62.0 vol% 316L stainless steel powder + 30.0 vol% POM + 6.0 vol% LDPE + 1.2 vol% HDPE + 0.8 vol% EVA (ethylene-vinyl acetate copolymer). Two separate preforms were injection molded using a metal powder injection molding process. The injection temperature was 185℃, the injection pressure was 115 MPa, and the holding time was 3 seconds, yielding qualified preforms. The bonding surfaces of the two preforms were then polished with 1000-grit sandpaper to control the surface roughness to 1.0~1.5 μm.
[0051] (2) Prepare adhesive mortar.
[0052] The adhesive slurry uses 304L stainless steel powder as the bonding powder (different melting point powders; 316L stainless steel powder has a melting point of 1390℃, and 304L stainless steel powder has a melting point of 1380℃, a difference of 10℃). The mass ratio of the adhesive slurry is: acrylic resin 32%, polyethylene glycol 10%, polyether-based silicone-free defoamer 3%, and 304L stainless steel powder 55%. All components are added to a vacuum mixer and stirred under vacuum at room temperature for 25 minutes at a stirring speed of 80 r / min to prepare an adhesive slurry with suitable flowability and viscosity.
[0053] (3) Adhesive assembly and forming.
[0054] Using a scraper coater, the adhesive slurry is evenly applied to the bonding surface of the two separate blanks. The coating thickness is precisely controlled to 0.15mm. After coating, the two separate parts are quickly joined together. The surface tension of the slurry automatically aligns and calibrates the parts. After standing at room temperature for 20 minutes, the physical bonding of the two separate blanks is completed, resulting in a tight and gapless bond.
[0055] (4) Integrated degreasing treatment.
[0056] The assembled green body is subjected to a combined process of nitric acid catalytic degreasing and thermal degreasing. First, catalytic degreasing is performed at a temperature of 150℃ for 12 hours. Then, thermal degreasing is performed by raising the temperature to 600℃ and holding it for 2 hours to completely remove the binder and organic components of the slurry in the green body and avoid oxidation and deformation of the green body.
[0057] (5) Integrated sintering treatment.
[0058] After degreasing, the whole unit is sintered at a temperature of 1385~1390℃ and held for 2-3 hours. Then it is cooled to room temperature in the furnace.
[0059] The finished product has a complete hollow structure with continuous and defect-free grains at the bonding interface, achieving integrated metallurgical bonding. The structural components have a tensile strength of 850MPa, excellent corrosion resistance, no leakage under high-pressure immersion conditions, and dimensional deformation of <0.02mm. They are suitable for harsh working conditions such as high salt spray and humidity, and the yield rate in mass production is 97.5%.
[0060] Example 3 Example 3 provides a method for split-bonding molding of complex hollow PIM structural parts, used to prepare thin-walled irregular cavity precision PIM parts, including the following steps: (1) Preparation of split blanks.
[0061] Using thin-walled, irregularly shaped cavity precision PIM parts as the processing object, it is divided into two separate structures: an upper cavity and a lower cavity. Aluminum nitride ceramic powder is used as the matrix material, and a plastic-based binder is used. The injection molding materials include the following volume fractions: aluminum nitride ceramic powder 54.0 vol% + POM (polyoxymethylene) 32.0 vol% + microcrystalline wax MW 8 vol% + LDPE (low-density polyethylene) 4.0 vol% + HDPE (high-density polyethylene) 1.2 vol% + stearic acid SA 0.8 vol%. The separate preforms are prepared using conventional PIM injection molding technology, with an injection temperature of 175-190℃ and an injection pressure of 65-80MPa for segmented injection.
[0062] Subsequently, the bonding surfaces of the two separate blanks are roughened by grinding, with the roughness controlled at 1.3~1.9μm, to remove the surface oxide layer and impurities and ensure the bonding effect of the bonding interface.
[0063] (2) Prepare adhesive mortar.
[0064] The adhesive slurry uses aluminum nitride ceramic powder as the bonding powder (the same as the matrix powder in the split preform). The mass ratio of the adhesive slurry is: 38% colloidal acrylic resin, 4% polyether-modified silicone defoamer, 6% polyvinyl alcohol, and 52% aluminum nitride ceramic powder. After mixing the components, the mixture is vacuum stirred for 35 minutes at a speed of 120 r / min to prepare a colloidal adhesive slurry with strong stability and excellent wettability.
[0065] (3) Adhesive assembly and forming.
[0066] The slurry is evenly applied to the bonding surface of the split blanks with a coating thickness of 1 mm. After coating, the split blanks are quickly joined together. The excellent surface tension and viscosity of the slurry are used to achieve automatic bonding and positioning. The blanks are left to stand at room temperature for 25 minutes to allow the interface to fully bond and initially cure and shape.
[0067] (4) Integrated degreasing treatment.
[0068] The assembled green body is subjected to a combined process of oxalic acid catalytic degreasing and thermal degreasing. First, catalytic degreasing is performed at a temperature of 150℃ for 8 hours. Then, thermal degreasing is performed by raising the temperature to 650℃ and holding it for 2 hours to completely remove the binder and organic components of the slurry in the green body and avoid oxidation and deformation of the green body.
[0069] (5) Integrated sintering treatment.
[0070] After degreasing, the entire piece is sintered at a temperature of 1850℃ for 2-3 hours and then cooled to room temperature in the furnace.
[0071] The finished product has a complete and undeformed structure, with no delamination or pores at the bonding interface, and uniform and continuous grain growth. The bonding surface exhibits excellent sealing performance without affecting the material's physical properties, and the process demonstrates good stability, making it suitable for mass production of thin-walled precision hollow parts.
[0072] The above are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape and principle of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a complex hollow PIM (partially bonded and molded) structural component, characterized in that, Includes the following steps: (1) Design the complex hollow structure as at least two separate injection molded parts, and prepare the separate blanks separately by powder injection molding process; (2) Prepare adhesive slurry, wherein the adhesive slurry includes adhesive powder and compound adhesive; (3) Apply the adhesive slurry evenly to the bonding surface of each separate blank, and combine the separate blanks into a whole blank; (4) Perform an integral degreasing treatment on the entire blank; (5) The degreased blank is sintered as a whole to form a complex hollow structure.
2. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 1, characterized in that, In step (2), the compound adhesive includes at least two of polyethylene glycol, polyvinyl alcohol, acrylic resin and defoamer.
3. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 1, characterized in that, In step (2), the bonding powder is the same as the matrix powder in the split blank.
4. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 1, characterized in that, In step (2), the bonding powder is a differentiated melting point powder with a melting point no more than 50°C lower than that of the matrix powder in the split blank.
5. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 4, characterized in that, In step (5), the temperature of the integral sintering treatment is not higher than the melting point of the matrix powder in the split blank, and not lower than the melting point of the differentiated melting point powder.
6. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 1, characterized in that, In step (3), the coating thickness of the adhesive slurry is 0.02~1mm.
7. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 1, characterized in that, It also includes a step of grinding and roughening the bonding surface of the split blank before step (3).
8. The method for preparing a complex hollow PIM (partially bonded and molded) structural component according to claim 1, characterized in that, The matrix powder in the split blank is MIM metal powder or ceramic powder.
9. A complex hollow structural component, characterized in that, It is manufactured using the method for preparing a split-bonded molded PIM complex hollow structural component as described in any one of claims 1-8.
10. The complex hollow structural component according to claim 9, characterized in that, The complex hollow structural components are thin-walled or medium-thick-walled structural components, spiral-patterned structural components, and irregularly shaped closed cavity PIM precision parts.
